Correlation between metabolomic profile and proliferation of Macrobrachium rosenbergii primary embryonic cell culture - Sudarshan, Gurucharan; Weil, Simy; Jasińska, Weronika; Manor, Rivka; Goldstein, Oron; Aflalo, Eliahu D.; Ofir, Rivka; Zimin, Sean V.; Levy, Tom; Rosental, Benyamin; Brotman, Yariv; Sagi, Amir (Frontiers in Marine Science, 2023)
Short-term embryonic cell culture of the prawn Macrobrachium rosenbergii reveals unique relationships between the lipidomic content of the culture media and the cells' proliferation phase. The cultures were monitored for metabolic activity, cell cycle analysis, and for the first time in prawns: changes in lipid metabolic footprint in the culture media using Mass spectrometry. This analysis allowed us to study the relationship between the presence or absence of specific metabolites to the cell-cycle and proliferation status of cultures. The three commercial media studied, sustained cellular metabolic activity, with a peak at day 4 in either DMEM high glucose or Opti-MEM and a peak at day 7 for DMEM:F12. The primary culture growing in Opti-MEM presented the shortest doubling time, making this media most appropriate for short-term culture. DMEM high glucose retained a higher count of attached cells in the plate at day 1 and had the highest count of cells at day 4, with an increasing tendency towards the G2/M phase. Lipidomic analysis of Opti-MEM showed significantly higher concentrations of 26 annotated lipids compared to the other two media. Specific lipid signaling molecules like phosphatidylcholine and phosphatidylserine were found to be the most abundant in all the three media cultured with cells. Palmitate levels in all media cultured with cells were correlated to the cultures' proliferation phase. Since we detected this lipid in higher relative abundance in Opti-MEM compared to the other media, cells growing in the other two media probably needed to synthesize it as a precursor of membrane complex lipids. These novel findings will contribute to the longtime goal of establishing sustainable crustacean cell-culture lines and could facilitate precision in conditioning of culture media towards sustainable growth and proliferation and delaying cells from entering the quiescence phase.